Analisis Efisiensi Penggunaan Input Produksi Usahatani Semangka Di Desa Maranatha Kecamatan Sigi Biromaru Kabupaten Sigi - Laksmayani, Made Krisna; Laapo, Alimudin; H., Sulaeman (AGROTEKBIS, 2013)
This study aims to determine the influence of the use of input and determine the level of efficiency of use of inputs of land, seed, labor, fertilizer Phonska, ZA, Pearl fertilizer, and fertilizer to the production of KCl Watermelon in Maranatha Village District Biromaru Sigi Sigi. The research was conducted at Maranatha Village District Biromaru Sigi Sigi. Respondents were 36 people, which was conducted by the census. Analysis tool used is the Cobb-Douglass Production Function and Efficiency Analysis. The results showed simultaneously all the independent variables (X) effect nayata the dependent variable (Y). partial land area (X1), seeds (X2), labor (X3), fertilizer Phonska (X4), ZA (X5), fertilizer Pearl (X6), and KCl (X7) significantly affect the production of watermelon in the Village Maranatha District Biromaru Sigi Sigi sig value 0.000 <0.01 at ? 1%. Efficiency analysis results show the value of the variable k land, seed, labor, fertilizer Phonska, ZA, fertilizer Pearls, and KCl show number > 1, meaning that all inputs used in the production of watermelon farming in Maranatha Village District Sigi Sigi Biromaru in terms of the price of each input production efficiency declared yet.